[tex]T=\frac{2}{2^{1}}+\frac{3}{2^{2}}+\frac{4}{2^{3}}+...+\frac{2015}{2^{2014}}\\\frac{1}{2}T=\frac{2}{2^{2}}+\frac{3}{2^{3}}+\frac{4}{2^{4}}+...+\frac{2015}{2^{2015}}\\\rightarrow \frac{1}{2}T=1+(\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{2014}})-\frac{2015}{2^{2015}}\\B=\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{2014}}\\2B=\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2013}}\\\rightarrow B=\frac{1}{2}-\frac{1}{2^{2014}}<\frac{1}{2}\\\rightarrow \frac{1}{2}T=1+(\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{2014}})-\frac{2015}{2^{2015}}=1+B-\frac{2015}{2^{2015}}<1+\frac{1}{2}-\frac{2015}{2^{2015}}<1+\frac{1}{2}=\frac{3}{2}\\\rightarrow \frac{1}{2}T<\frac{3}{2}\rightarrow T<3[/tex]